Emergence of form from function—Mechanical engineering approaches to probe the role of stem cell mechanoadaptation in sealing cell fate. Issue 5 (2nd September 2016) - Knothe Tate, Melissa L.; Gunning, Peter W.; Sansalone, Vittorio
ABSTRACT: Stem cell "mechanomics" refers to the effect of mechanical cues on stem cell and matrix biology, where cell shape and fate are intrinsic manifestations of form and function. Before specialization, the stem cell itself serves as a sensor and actuator; its structure emerges from its local mechanical milieu as the cell adapts over time. Coupling of novel spatiotemporal imaging and computational methods allows for linking of the energy of adaptation to the structure, biology and mechanical function of the cell. Cutting edge imaging methods enable probing of mechanisms by which stem cells' emergent anisotropic architecture and fate commitment occurs. A novel cell-scale model provides a mechanistic framework to describe stem cell growth and remodeling through mechanical feedback; making use of a generalized virtual power principle, the model accounts for the rate of doing work or the rate of using energy to effect the work. This coupled approach provides a basis to elucidate mechanisms underlying the stem cell's innate capacity to adapt to mechanical stimuli as well as the role of mechanoadaptation in lineage commitment. An understanding of stem cell mechanoadaptation is key to deciphering lineage commitment, during prenatal development, postnatal wound healing, and engineering of tissues.